Stochastic Approximation for Identification of Multivariable Systems - El-Sherief, Hossny E. (My University, 1977)
In this thesis a non-parametric normalized stochastic approximation algorithm has been developed for the identification of multivariable systems from noisy data without prior knowledge of the statistics of measurement noise.
The system model is first transformed into a special canonical form, then it is formulated in a non-parametric form. The parameters of this model are estimated through a normalized stochastic approximation algorithm. Finally, the system parameters are recovered from these estimates by another transformation.
The proposed algorithm is applied to the identification of two simulated systems.
Conclusions of this work and suggestions for future work are given.
Keywords: non-parametric, stochastic, approximation, multivariable, identification